Kerk en volk - Wyk, D. J. C. van (Hervormde teologiese studies, 1991)
Church and nation In this essay the relationship between the church and the nation, is once more investigated. It has become necessary in the light of the fact that the concept of ‘nation’ is being treated more and more negatively, especially in the ecumenical theology of mission and the struggle against apartheid in South Africa. The background to this negative attitude is not only the racial situation in South Africa, but also the experiences of church and theology in Nazi Germany. The conclusion at which the author arrives, is that, because of its assosiation with apartheid in South Africa, the word ‘nation’ has became more and more a curse. This attutude is irresponsible, and not in line with biblical thought.